Peningkatan Kemampuan Administrasi Tender Pengadaan Barang/Jasa Pemerintah di Bidang Jasa Konstruksi - Zaenal Arifin; Diah Sulistyani Ratna Sediati; Soegianto Soegianto (Journal of Dedicators Community, 2020)
The purpose of this community service is to improve the ability to hold tenders for goods/ service providers in the construction service sector. The Association of National Construction Entrepreneurs (Gapensi) Semarang City as a community service partner is 348 people divided into 7 classifications. Some of the reasons for goods and service providers who are members of Gapensi fail to win tenders are 1) a lack of understanding of the development of existing regulations related to the procurement of goods/ services that often change; 2) administrative errors in completing the auction for the procurement of goods and services; 3) Providers of goods/ services are usually left to one administrative person so that the owner of the business entity never knows the procedure or mechanism and completeness of the procurement of government goods/ services. The method used in this service is the socialization of the latest procurement of goods/ services and training in the governance of government procurement of goods/ services. The result of this service is that Gapensi members know the good governance of government procurement of goods and services and are able to practice in tenders.